Educational inclusion of migrants/refugees. Secondary school teachers' views - GIAVRIMIS PANAGIOTIS (Social Sciences and Education Research Review)
Including immigrants and refugees in the host countries' education is an educational process encompassing political, social, and individual processes. Teachers, as an essential factor in the socialisation and inclusion of students in a particular society, play a mediating role in including students with migrant and refugee backgrounds. This study aimed to research the views of secondary school teachers in the Greek educational system regarding including migrant and refugee students in it. The participants were fourteen secondary school teachers. Qualitative research was chosen as a design of the research to investigate the teachers' views deeply. A semi-structured interview was used as a research tool. The analysis of the teachers' interviews revealed that most are positive towards including migrant and refugee students. Still, they consider using the Greek language as a prerequisite for inclusion. However, due to issues related to biosomatic and educational factors, some of the study teachers reported objections. Insufficient and inadequate educational policy plays a mediating role in shaping the above arguments.